Physical Activity of Referees and Assistant Referees at Indonesian Football League 2019/2020 - Bangbang Syamsudar; Yudi Nurcahya (International Journal of Artificial Intelligence Research, 2022)
This study used an ex-postfacto descriptive study research method. The research instrument used a heart rate monitor based on the POLAR M600 smartwatch with Global Positioning System sensors to calculate the total distance traveled by the referee and the assistant referee, the average of the maximum speed, and analyze the physical intensity performed by the referee during leading a match to measure physical fitness. Data analysis used Normality Test and Norms Reference Assessment. The purpose of this study was to determine the physical activity profile of the referees and assistant referees when serving in Liga 1 Shopee 2019/2020. The physical activities of 5 referees (FIFA) and 7 assistant referees (FIFA) were analyzed in 12 shopee league 1 matches in the period January to March 2020 with the status of the top-ranked match. The results of the findings of this study indicate that the distance traveled by the referee is greater than that of the assistant referee. The average heart rate of the referee is higher than that of the assistant referee, and the maximum average heart rate of the referee is greater than that of the assistant referee. Then the maximum speed of the assistant referee is higher than the maximum speed of the referee. In general, the referee's average running speed is higher than the assistant referee's average speed. In conclusion, there is a difference between physical activity between the referee and the assistant referee. Therefore, a different fitness training program is needed to prepare them to lead the match